Bagaimana E-book â€œChemistry Challengeâ€ Mempengaruhi Profil Literasi Bahan Kimia? Kajian untuk Menguji Efektivitas Media Pembelajaran - Faiz Ilham Pratama; Eli Rohaeti (Postgraduate, University of Mataram, 2024)
The appropriate utilization of media can greatly impact one's chemical literacy. A prior study involved the development of an e-book called